Narrative in teaching-learning processes through the virtual worlds of the metaverse - Alessandra Natalini; Fabio Orecchio; Donella Giuliani (Pensa MultiMedia, 2024)
This study highlights the importance of using the metaverse in education, demonstrating how it stands out by transforming narrative into a more accessible and engaging experience. The key innovation of this approach lies in the creation of interactive narrative experiences that amplify student interest and improve their comprehension of texts. Although this requires significant preparation from teachers, the benefits in terms of student engagement justify the adoption of these cutting-edge technologies. The importance of increasing research in this area lies in its ability to demonstrate, through evidence, how education can be transformed by leveraging technologies like the metaverse to enhance narrative skills and make the comprehension of texts easier.